Intellectual Disability - Whitaker, S. author. aut Link
VIII, 199 p.
Keywords: The current construct of intellectual disability is based on the assumption that both IQ and adaptive behaviour can be measured accurately. Intellectual Disability explains how and why this is not fit for purpose and that it is actually neither necessary nor reasonable to have a single construct of intellectual disability.